The internet of value: Towards a definition, framework, and understanding of its sustainability implications - Lohmer, Jacob; Birkel, Hendrik; Müller, Julian (Technological Forecasting and Social Change, 2024)
The internet of value (IoV) is predicted to have the potential for disruptive changes in monetary values, goods, and information sharing. Thus, it could fundamentally affect organizations, business models, operations, and employees. However, the concept and definition of the IoV and its potential in all dimensions of the triple bottom line of sustainability remain opaque. In response, we conducted eleven expert interviews to develop a comprehensive understanding of the IoV, including a definition, implications, prerequisites, and risks, emphasizing sustainability potentials. The findings highlight different perspectives on the concept of the IoV and the synergies of technologies such as blockchain, the internet of things, and artificial intelligence. Further, digital platforms, tokenization, and smart contracts are analyzed to develop a holistic IoV framework. In doing so, we aim to critically evaluate the IoV and its potential impacts on researchers and practitioners. In particular, the iterative refinement and interplay of technologies, concepts, and barriers support a common understanding of the concept of an IoV and facilitate goal-oriented development. These are further underpinned by the research avenues developed to induce investigations across different research fields.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Blockchain technology; Digital platforms; Internet of value; Smart contracts; Sustainability; Tokenization